Chronic fatigue syndrome revisited - Neki, NS (Bangladesh Journal of Medical Science, 2016)
Chronic fatigue syndrome (CFS) is a common and disabling problem; although most likely of biopsychosocial origin. The nature of the pathophysiological components remains unclear. It is an illness characterized by persistent and relapsing fatigue, often accompanied by numerous symptoms involving various body systems. The etiology of CFS remains unclear. Celiac disease can present with neurological symptoms in the absence of gastrointestinal symptoms; therefore, celiac disease should be included in the differential diagnosis of CFS. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.326-328